CHML regulates migration and invasion in hepatocellular carcinoma via transcriptional and metabolic reprogramming - Cao, Huanqian; Wang, Siyu; Zhang, Li; Xie, Heying; Liu, Yiqiong; Kong, Ruijiao; Jia, Yin; Lu, Ling; Jiang, Junfeng; Liu, Shanrong (Frontiers in Oncology, 2025)
BackgroundHepatocellular carcinoma (HCC), a prevalent malignant neoplasm, presents significant therapeutic challenges. However, the key factors and mechanisms driving HCC metastasis remain incompletely understood. This study aimed to elucidate the mechanism through which CHML regulates the migration and invasion of HCC cells.MethodsFollowing CHML knockout or overexpression, we assessed the proliferative capacity of HCC cells using the Cell Counting Kit-8 (CCK-8) assay, 5-ethynyl-2′-deoxyuridine (EdU) incorporation, colony formation assay, and subcutaneous xenograft tumor models in nude mice. Cell migration and invasion were evaluated using wound healing and Transwell assays. We utilized transcriptome sequencing and untargeted metabolomics to assess the gene's effects on transcriptomic and metabolic changes and its mechanisms in regulating migration.ResultsCHML knockout significantly inhibited the migration and invasion of HCC cells in vitro, whereas CHML overexpression promoted these phenotypes (P<0.05). Transcriptomic sequencing revealed CHML-mediated regulation of migration-associated pathways, whereas untargeted metabolomics identified choline metabolism as a key significantly altered pathway. Notably, the integration of transcriptomics and untargeted metabolomics identified choline metabolism as a pivotal pathway in CHML-regulated migration and invasion. The subsequent mechanistic analysis demonstrated that CHML upregulated the Solute carrier family 44 member 3 (SLC44A3) to enhance choline uptake, thereby increasing phosphatidic acid (PA) production. This metabolic shift activated MAPK and PI3K-AKT signaling cascades, ultimately driving HCC cell migration and invasion.ConclusionCHML promoted the migration and invasion of HCC cells through multiple pathways. Our findings provide novel insights into metabolic dependencies in HCC metastasis and position CHML as a promising therapeutic target.